Processos de (des)identificação no/do Pibid: Efeitos de sentido na formação inicial de professores de língua estrangeira - Souza, Lara Cristina Batista (2024)
Regarding the field of language teacher education, the discourse studies developed in Brazil have been addressing the teacher-subject position, attempting to comprehend the meaning effects produced by subjection and the interpellations that occur throughout this process. Therefore, matters of language, identity, and foreign language teaching and learning emerge to problematize, to question, and to tension the knowledge produced in the field of Applied Linguistics. Based on this concern, I proposed this research, which aimed to investigate the meaning effects produced by the discourses that interpellate the document of the PIBID language subproject (edition no. 23/2022) at UFU and affect the teacher representations, identified in the identity constitution of the undergraduate students taking part in the program. Hence, the corpus consisted of the document of the aforementioned subproject, with the purpose of investigating the meaning effects of the document, and the transcription of semi-structured interviews conducted with five PIBID participants, which were carried out upon the participants' first stages into the program. Based on the concept of discursive representation, I sought to discuss the teacher representations that emerged through the subproject’s document, as well as to analyze the teacher representations from the PIBID participants’ utterances, which I gathered from the interview transcriptions. My hypothesis is that the program presents itself as a favorable and relevant instance, that enables identifications in the identity constitutions of the participants in favor of the appreciation of the teaching career. I relied on theories of Franco-Brazilian Discourse Analysis, in addition to the crossings of Freudian-Lacanian Psychoanalysis in this field, to perform my interpretative gestures. As a result of the analysis, I identified three teacher representations in the subproject’s document, which were: the devalued teacher; the incomplete teacher; the critical-reflexive citizen teacher. Moreover, the analysis of the PIBID participants’ utterances allowed me to delineate three other representations, namely: the messianic teacher; the animator and mediator teacher; the discredited teacher. The interweaving of the discussions of the analyses made from the subproject’s document and the utterances of the PIBID participants emphasized that, due to discursive heterogeneity, the context of teacher education is crossed by encounters-confrontations. Although PIBID aims at the valorization of the teaching career, the discourses that cross the subproject’s document and weave the network of meanings of the PIBID participants’ utterances resonate the representation of the devalued teacher and the discredited teacher. However, it is the encounters-confrontations in the teacher education process that make possible the (dis)identifications of the subject-teachers in PIBID, thus, allowing them to produce meanings and signify (from) the language teacher position.